Self-compassion and Pre-competition Anxiety in Martial Arts Student Athletes - Mahmoud Mohebi; Athena Gharayagh Zandi; Sahar Zarei; Hassan Gharayagh Zandi (Sport Sciences and Health Research)
Introduction: The present study aimed to investigate the relationship between Self-compassion and precompetitive anxiety among female athlete students.Methods: This was a descriptive correlational study. Two hundred and fifty-three female students (140 taekwondo & 113 karate) were selected among athletes present at the 14th Student Cultural Sports Olympiad. Self-compassion Scale and Competitive State Anxiety–2 were used in this study before competing in games to measure the aforementioned theoretical constructs.Results: The obtained results revealed a significant relationship between pre-competitive anxiety and Self-compassion. Moreover, the components of this characteristic positively predicted self-confidence variance; however, this prediction reversed with somatic and cognitive anxiety.Conclusion: Based on the current study results, Self-compassion plays a moderating role in the pre-competitive anxiety of female martial arts athletes. Therefore, improving this characteristic should be considered to promote self-confidence and reduce the pre-competitive anxiety in these athletes.